2015
DOI: 10.1007/s00216-015-8573-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glucuronide and sulfate steroids in urine by ultra-high-performance supercritical-fluid chromatography hyphenated tandem mass spectrometry

Abstract: Profiling conjugated urinary steroids to detect anabolic-steroid misuse is recognized as an efficient analytical strategy in both chemical-food-safety and anti-doping fields. The relevance and robustness of such profiling rely on the analysis of glucuronide and sulfate steroids, which is expected to have properties including accuracy, specificity, sensitivity, and, if possible, rapidity. In this context, the ability of ultra-high-performance supercritical-fluid chromatography (UHPSFC) hyphenated tandem mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…The ‘steroid profile’, a set of endogenous steroids used as markers for testosterone abuse, is analysed concurrently and the use of E. coli is a regulatory requirement for these steroids. Recent publications however have illustrated the potential advantage of detecting sulfates for long‐term detection of steroid abuse, which resulted in a further increased research focus . In this light, the excretion form of the two new long‐term metabolites, oxyM9 and mestM22, was investigated.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The ‘steroid profile’, a set of endogenous steroids used as markers for testosterone abuse, is analysed concurrently and the use of E. coli is a regulatory requirement for these steroids. Recent publications however have illustrated the potential advantage of detecting sulfates for long‐term detection of steroid abuse, which resulted in a further increased research focus . In this light, the excretion form of the two new long‐term metabolites, oxyM9 and mestM22, was investigated.…”
Section: Resultssupporting
confidence: 74%
“…Recent publications however have illustrated the potential advantage of detecting sulfates for long-term detection of steroid abuse, which resulted in a further increased research focus. [38][39][40][41][42][43][44][45] In this light, the excretion form of the two new long-term metabolites, oxyM9 and mestM22, was investigated. Excretion urine samples were prepared with β-glucuronidase (from E. coli), β-glucuronidase/aryl sulfatase (from H. pomatia) and without enzyme, resulting in the free + glucuronide fraction, free + glucuronide + sulfate fraction and free steroid fraction, respectively.…”
Section: Long-term Metabolite Excretion Formmentioning
confidence: 99%
“…7,18,19 The most important parameter influencing the retention of the analytes was the chemistry of the stationary phase. 13,16 In spite of the fair availability of different UPC 2 columns, with known chemistry of the stationary phases, selecting the best column for the method development still remains challenging. 11 Mass spectrometric sensitivity and overall chromatographic resolution of the target analytes including geometrical isomers such as PGD 2 and PGE 2 provided a basis for the selection of column.…”
Section: Resultsmentioning
confidence: 99%
“…9,11 Over the years, many studies have demonstrated successful application of SFC for the separation of diverse species of lipids including phospholipids, lysophospholipids, sphingolipids, ceramides, glycerolipids, 10,12 vitamins, 13 fatty acids, 14 oxylipins, 15 and steroids. 16 More importantly, the use of SFC has enabled the comprehensive separation of isomers in very short run time. 11,13,14 Under such context, the aim of this study was to develop a fully validated supercritical fluid chromatography-tandem mass spectrometry method (SFC-MS/ MS) for the rapid identification and quantification of a number of endogenous eicosanoids.…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical fluid chromatography (SFC) [16] represents an interesting separation alternative that has already shown its potential in enhancing detection performances of residues of growth promoters. [17] Using mainly liquid carbon dioxide as a mobile phase, this separation technique is based on similar retention mechanisms of both gas and liquid chromatography, depending on the mobile phase density, the flow rate, the column temperature and the stationary phase's properties [18] with a larger range of solvent selectivity choice. De facto, it enables an increased separation of relatively similar and numerous chemical compounds as described in for peptides,, [19] drugs, chiral or not, [20] or even lipids separation.…”
Section: Introductionmentioning
confidence: 99%